Front Cover: Asymmetric Synthesis of 3‐Pyrrolines through an Aryne‐Induced Domino Process (Asian J. Org. Chem. 4/2021). Issue 4 (9th April 2021) - Hwu, Jih Ru; Panja, Avijit; Gupta, Nitesh K.; Huang, Wen‐Chieh; Hu, Yu‐Chen; Lin, Chun‐Cheng; Hwang, Kuo‐Chu; Chan, Wei‐Jen; Tsay, Shwu‐Chen
Abstract : A new domino reaction is developed for the synthesis of optically active 3‐pyrrolines. The reaction involves the use of (trimethylsilyl)aryl triflates, KF, Schiff bases, and alkynes in the presence of a chiral catalyst (R)‐(–)‐1, 1′‐binaphthyl‐2, 2′‐diyl hydrogenphosphate. The key features of this reaction include the generation of a single product in very good yields with high stereo‐ and enantioselectivity. The enantiomeric ratio reaches as high as 98.5:1.5. The overall pathway includes four steps in a domino process of 1, 2‐elimination, 1, 2‐nucleophilic addition, 1, 4‐proton shift, and (3+2) cycloaddition. More information can be found in the Full Paper by Jih Ru Hwu et al.